The Unlocking Language Proficiency: Exploring Duolingo's Impact on Vocabulary Learning - Indrasari, Hesti Aulia; Prasetyo, Yudy; Putranto, Henry Rio (Jetlal, 2024)
The development of technology in the industry 4.0 era makes it easy for students to carry out learning activities. There are several applications that can help students learn English, especially learning vocabulary. This research used Duolingo application media as a medium for learning English vocabulary. The purposes of this research were to implement the Duolingo application to learn English vocabulary in STAR course for junior high school students and to investigate the student’s perceptions about their learning experience after used Duolingo application. This research used descriptive qualitative research methods. The sample in this research was 10 grade 7 junior high school students. Researchers used observation, interviews, and documentation as data collection. The sample in this research was 10 grade 7 junior high school students. The results of this research showed that all students in the STAR course could understand all the instructions on how to use Duolingo and they all felt happy to use it as a medium for learning English vocabulary. However, 2 students encountered the challenge that the disruption of the internet network could hinder the use of Duolingo. According to student’s percaptions, Duolingo was praised for its entertaining features and effective vocabulary practice, it is essential to address issues such as advertisements and internet dependency for an enhanced user experience.